Sistem Terintegrasi BOQ dan Purchase Order pada Telkom Akses Tasikmalaya - Tegar Hikmah; Acep Irham Gufroni; Cecep Muhamad Sidik Ramdani (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
The management of Bill of Quantity (BOQ) and purchase order processes at PT. Telkom Akses Tasikmalaya still faces several issues, including repetitive data entry, potential calculation inconsistencies, separated stock monitoring, and document validation that has not been centrally documented. These conditions indicate that administrative digitalization should not merely transform manual documents into electronic forms, but must also integrate data flows and operational processes. This study aims to develop a web-based integrated BOQ and purchase order system using the Laravel framework and Agile method. Data were collected through observation, interviews, and literature study, while system validation was conducted using Black Box Testing. The developed system includes project data input, designator management, BOQ calculation, cost recapitulation, Word document export, document upload and correction, stock monitoring, and an Executive Information System dashboard. The testing results show that all user-side functional scenarios worked as expected. The system contributes by connecting BOQ, purchase order, document management, stock monitoring, and dashboard reporting into a centralized platform. However, this study is limited to functional validation; therefore, further testing on usability, security, performance, and work efficiency is required.